Haemostatic Platelet Plug Formation in the Isolated Rabbit Mesenteric Preparation - An Analysis of Red Blood Cell Participation - Bergqvist, D; Arfors, K-E (Thrombosis and Haemostasis, 1980)
In a model using an isolated rabbit mesenteric preparation microvessels were transected and the time until haemostatic plugs formed was registered. Perfusion of platelet rich plasma gave no haemostasis whereas whole blood did. Addition of chlorpromazine or adenosine to the whole blood significantly prolonged the time for haemostasis, and addition of ADP to the platelet rich plasma significantly shortened it. It is concluded that red cells are necessary for a normal haemostasis in this model, probably by a combination of a haemodynamic and ADP releasing effect.The fundamental role of platelets in haemostatic plug formation is unquestionable but there are still problems concerning the stimulus for this process to start. Three platelet aggregating substances have been discussed – thrombin, adenosine diphosphate (ADP) and collagen. Evidence speaking in favour of thrombin is, however, very minimal, and the discussion has to be focused on collagen and ADP. In an in vitro system using polyethylene tubings we have shown that "haemostasis" can be obtained without the presence of collagen but against these results can be argued that it is only another in vitro test for platelet aggregation (1).To be able to induce haemostasis in this model, however, the presence of red blood cells is necessary. To further study this problem we have developed a model where haemostatic plug formation can be studied in the isolated rabbit mesentery and we have briefly reported on this (2).Thus, it is possible to perfuse the vessels with whole blood as well as with platelet rich plasma (PRP) and different pharmacological agents of importance.
Keywords: Platelet plug; Rabbit